2014
DOI: 10.1515/chem-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous radiolysis of urea. Implications in astrobiology and prebiotic chemistry

Abstract: Abstract:Urea is an organic molecule present in most living organisms. Historically, it was the first organic molecule synthesized in the laboratory. In prebiotic chemistry, urea readily forms in different laboratory simulations using different energy sources. Furthermore, the role of solid surfaces, particularly minerals, might have been crucial to increase the complexity of the organic matter which may have led to the subsequent emergence of life on Earth.In this work, the radiolysis of urea in presence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The presence of urea increased the conversion of the substrate in the case of NWA 4482 and Al‐Haggunia. Unconverted urea (50–90 % with respect to the initial amount) was also detected in the reaction mixture, in accordance with the relative stability shown by this compound toward ionizing radiation once adsorbed on the surface of minerals [49] . Regarding the chemoselectivity of the reaction, the presence of urea decreased significantly the total yield of monomeric derivatives in the case of Al‐Haggunia (Table 2, entry 6 versus entry 3).…”
Section: Resultssupporting
confidence: 68%
“…The presence of urea increased the conversion of the substrate in the case of NWA 4482 and Al‐Haggunia. Unconverted urea (50–90 % with respect to the initial amount) was also detected in the reaction mixture, in accordance with the relative stability shown by this compound toward ionizing radiation once adsorbed on the surface of minerals [49] . Regarding the chemoselectivity of the reaction, the presence of urea decreased significantly the total yield of monomeric derivatives in the case of Al‐Haggunia (Table 2, entry 6 versus entry 3).…”
Section: Resultssupporting
confidence: 68%
“…Seino et al, noted that radiolytic yield of hydrogen depends on gamma radiation dose absorbed and metal oxide particle size [9,10]. Radiolysis of urea aqueous solutions was studied before in different workers [11][12][13][14][15][16]. Urea is relatively stable to ionizing radiation in aqueous solutions up to 20 kGy [11].…”
Section: Introductionmentioning
confidence: 99%
“…Radiolysis of urea aqueous solutions was studied before in different workers [11][12][13][14][15][16]. Urea is relatively stable to ionizing radiation in aqueous solutions up to 20 kGy [11]. Moreover, it was reported that the RIC of urea aqueous solutions significantly increases upon radiolysis [12,13].…”
Section: Introductionmentioning
confidence: 99%